1993
DOI: 10.1016/0014-5793(93)80191-v
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose‐6‐phosphate, a new regulator of yeast glycolysis that inhibits hexokinases

Abstract: Tre~lo~6-phosphate (P) ~mpetitively inhibited the hexokinases from ~~cc~omyee~ cerevisiae. The strongest inhibition was observed upon hexokinase II, with a K, of 40 FM, while in the case of hexoklnase I the K, was 200 NM. Glucokinase was not inhibited by trehalose-6-P up to 5 mM. This inhibition appears to have physiological significance, since the intracellular levels of trehalose-6-P were about 0.2 mM. Hexokinases from other organisms were also inhibited, while glucokinases were unaffected. The hexokinase fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
242
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 298 publications
(253 citation statements)
references
References 22 publications
(1 reference statement)
9
242
1
Order By: Relevance
“…T6P is an intermediate in trehalose biosynthesis that has been shown to possess regulatory potential (5,26 (7,21,22,47,53,59) and give further insights into T6P. In C. albicans, the tps2 mutant flocculates during stationary growth, while in A. nidulans, the mutant produces nonviable germination of spores through a deficiency in chitin production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T6P is an intermediate in trehalose biosynthesis that has been shown to possess regulatory potential (5,26 (7,21,22,47,53,59) and give further insights into T6P. In C. albicans, the tps2 mutant flocculates during stationary growth, while in A. nidulans, the mutant produces nonviable germination of spores through a deficiency in chitin production.…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose can also act as a membrane protectant during stressful conditions (14). On the other hand, some investigators have suggested that trehalose might also act as a reserve carbon source (23,31,36,51) and that trehalose-6-phosphate (T6P) can regulate hexokinase II and thus glycolytic flux in some fungi (5). Although its use as an energy source remains somewhat controversial, it has been definitively linked to sporulation in fungi (37).…”
mentioning
confidence: 99%
“…Competitive inhibition by Tps1's metabolic product trehalose 6-phosphate may offer a mechanism [73]. In our model, as in all other published ones, no Tps1-mediated feedback mechanism was incorporated, as the feedback has not been characterized kinetically (see main text for the consequences).…”
Section: A C K N O W L E D G E M E N T Smentioning
confidence: 99%
“…Several mutations described earlier as fdp1, cif1, byp1, and glc6 have been shown to be alleles of the same gene and to exert a wide range of pleiotropic phenotypes (reviewed in Thevelein and Hohmann, 1995). An important phenotype of all these mutants (except glc6), however, is that they are unable to grow on glucose, apparently because of an uncontrolled influx of glucose into the glycolytic pathway (Van Aelst et al, 1991;Hohmann et al, 1993;Blá zquez et al, 1993;Blá zquez and Gancedo, 1994). At least three different models for this unexpected role of Tps1 (also called Ggs1 in this context) in the control of glycolysis have been presented, as follows.…”
Section: Introductionmentioning
confidence: 99%